Long‐term outcomes of sacral neuromodulation for lower urinary tract dysfunction: A 23‐year experience. Issue 1 (24th November 2020) - Gandhi, Shreyas; Gajewski, Jerzy B.; Koziarz, Alex; Almutairi, Sulaiman; Ali, Abdullah; Cox, Ashley
Abstract: Aims: To evaluate the long‐term outcomes of sacral neuromodulation (SNM), and patient characteristics that may predict long‐term success or complications. Methods: A single‐center retrospective cohort study was performed of all patients who underwent SNM testing and implantation. Outcome results, resolution of symptoms, and device removal were reported. Multivariable logistic regression was used to identify predictors of success. Cox proportional hazards model was used to identify predictors for device removal. Results: Four hundred and thrity four patients underwent SNM test phase of which 241 (median age 48.0 years, 91.7% [221/241] female) had device implantation and were followed up for median [range] time of 4.0 (3 months–20.5 years) years. Multivariable logistic regression showed that male gender (odds ratio: 0.314; 95% confidence interval: 0.164–0.601, p  = .0005) was independently associated with decreased peripheral nerve evaluation success. At final follow‐up for patients who originally had device implantation, median (interquartile range) percent of symptoms resolution of all patients was 60.0% (0%–90%) and 69.3% (167/241) had SNM successful outcomes. Cox proportional hazards model showed no difference for time to SNM device removal with respect to patient age, gender, or diagnosis. 69.3% (167/241) patients had at least 1 surgical re‐intervention. The most common reason at first surgical re‐intervention was lead change only (26.3%, 44/167). Conclusion: SNM is a minimally invasive procedure with good long‐term success rates. There is a high revision rate but overall, SNM has a good safety profile and excellent long‐term outcomes.